Dianella ensifolia (L.) DC. (Liliaceae) - a new angiospermic record for Bangladesh (Bangladesh Journal of Plant Taxonomy, 2009)
Not available.Keywords: Dianella ensifolia; New record; Bangladesh. DOI: 10.3329/bjpt.v16i2.3932 Bangladesh J. Plant Taxon. 16(2): 181-184, 2009 (December)